The Relationship between Social Support and Optimism among Athletes from Bandung City in the Provincial Sports Week Qualification Round - Intan Nur Amellia; Adang Suherman; Unun Umaran (Journal of Physical Education Health and Sport, 2025)
Athletes in competitive sports face high psychological demands, so factors such as social support and optimism are important in maintaining mental function and performance. This study seeks to investigate the association between social support and optimism in athletes, both overall and by sport type, specifically team athletes and individual athletes. The study employs a correlational quantitative technique and includes 47 athletes from Bandung City who competed in the 2025 PORPROV Qualification Round. The Athletes' Received Support Questionnaire (ARSQ) was used to measure social support, while the Life Orientation Test-Revised (LOT-R) was used to assess optimism. Data were gathered online and examined with descriptive statistics, reliability tests, normality tests, and Pearson's correlation. The findings revealed that social support was not significantly connected to optimism among athletes as a whole. Separate analyses revealed no significant association between social support and optimism in either team or individual athletes, however team athletes demonstrated a stronger relationship. These data suggest that athletes' optimism is affected by internal variables rather than social support from their training environment. This study underlines the need for more targeted psychological therapies, such as mental training and self-efficacy reinforcement, to boost athletes' optimism.